2006
DOI: 10.1213/01.ane.0000243391.05091.bb
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Neutrophil-Derived Inflammatory Response in the Airways During Cardiopulmonary Bypass

Abstract: Cardiopulmonary bypass (CPB) is believed to cause postoperative lung dysfunction. To more closely examine the inflammatory processes occurring in the airways during CPB, we serially measured inflammatory mediators, with the assistance of a new bronchoscopic microsample probe, in 11 patients undergoing repair of aortic arch aneurysms. Epithelial lining fluid (ELF) and arterial blood were sampled simultaneously after induction of anesthesia, at the time of pulmonary reperfusion, and at the end of surgery. A decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(39 reference statements)
0
4
1
Order By: Relevance
“…It has been shown that the epithelial lining fluid levels of IL 6, IL 8 and neutrophil elastase in the airway of patients after CPB did not correlate with the degree of hypoxemia in eleven patients who underwent aortic arch repair. [29] Our study did not show any benefit of ketamine on other outcome parameters such as use of inotropes or vasopressors, bleeding, blood transfusion, postoperative ventilation, incidence of arrhythmias and infection. But our study was not powered to detect these outcome variables.…”
Section: Resultscontrasting
confidence: 64%
“…It has been shown that the epithelial lining fluid levels of IL 6, IL 8 and neutrophil elastase in the airway of patients after CPB did not correlate with the degree of hypoxemia in eleven patients who underwent aortic arch repair. [29] Our study did not show any benefit of ketamine on other outcome parameters such as use of inotropes or vasopressors, bleeding, blood transfusion, postoperative ventilation, incidence of arrhythmias and infection. But our study was not powered to detect these outcome variables.…”
Section: Resultscontrasting
confidence: 64%
“…In our patients, postoperative depression of oxygenation was observed, including reduced PaO 2 /FiO 2 ratio and patients shifting from preoperative mild hypoxemia ( n = 12) to postoperative severe ( n = 3), moderate ( n = 16), and mild ( n = 6) hypoxemia. Based on the previous evidence of predominant neutrophil recruitment and activation following CPB [ 6 , 14 ], neutrophil-mediated MMP-9 activation [ 14 , 20 ], and MMP-involved acute lung injury [ 7 , 12 ], we hypothesized that MMP-9 activation may contribute to pulmonary dysfunction following CPB, which could be manifested by reduced PaO 2 /FiO 2 ratio. Eventually, our results demonstrated transient enhancement of MMP-9 concentrations at 4–6 hours following CPB, which, however, was not correlated with reduced postoperative PaO 2 /FiO 2 , indicating clinically short-term and insignificant influence on pulmonary function in our patients with elective cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The cessation of alveolar ventilation and ischemia-reperfusion injury leads to neutrophil activation [ 3 ] and trafficking to lung [ 4 ] and entrapment in the pulmonary capillaries. The released proteolytic enzymes, such as matrix metalloproteinase- (MMP-) 9, degrade alveolar basement membrane and matrix [ 5 ], facilitating neutrophil transmigration and protein extravasation into the interstitial tissue of lung [ 6 ]. Consequently, injury to the alveolar endothelium and alveolar-capillary barrier dysfunction as central events in the pathogenesis of acute lung injury [ 7 ] are manifested with postoperative pulmonary edema and abnormal gas exchange after cardiac surgery with CPB.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive deficits were thought to result from haemodynamic changes and the occurrence of cerebral microemboli, but growing evidence suggests an additional major contribution from the triggering of damaging inflammatory processes by surgical manipulation and/or by immune activation of cells in the extracorporeal circulation. There is an activation of leucocytes which can generate an imbalance in the production of pro‐ and anti‐inflammatory cytokines (Kotani et al. 2006), many of which are known to affect cerebral function.…”
mentioning
confidence: 99%